IATROGENIC BIRTH TRAUMA OF THE VISUAL ORGAN IN NEWBORNS - Нонна Марковна Шибельгут; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Наталья Анатольевна Батина; Светлана Ивановна Елгина; Елена Германовна Рудаева; Наталья Степановна Черных; Кира Борисовна Мозес (Мать и дитя в Кузбассе)
Birth eye trauma is a type of injury that can occur during the birth process due to various physical impacts on the newborn's eyeball. More serious eye injury can occur when using obstetric forceps. Birth eye trauma can have a variety of manifestations, ranging from superficial injuries such as abrasions and scratches to more serious ones such as damage to the cornea, internal structures of the eye, or even vision loss. This type of injury can leave long-term consequences, affecting vision and overall eye health in the future.